Overcoming refractive index limit of mesoscale light focusing by means of specular-reflection photonic nanojet - Geynts Yu. E. Yury Elmarovich; Zemlyanov A. A. Aleksandr Anatoljevich; Minin I. V. Igor Vladilenovich; Minin O. V. Oleg Vladilenovich (2020, 2020)
Title screen